Education in Phenomenological Perspective - Yosua Septerio Glorian Taran; Yaya Sunarya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education in a phenomenological perspective offers a deep approach to the learning process by emphasizing the subjective and direct experience of the individual. This approach is rooted in the philosophy developed by Edmund Husserl, who emphasized the importance of understanding phenomena as they appear in the individual's consciousness without prejudice or assumptions from outside. This article will discuss the background of phenomenology, the concept of 'the lifeworld', phenomenology as an epistemological school, and its application in educational discourse. The main goal is to provide a comprehensive understanding of the contribution of phenomenology in education and how this approach can enrich the teaching and learning process.